2018
DOI: 10.1136/bmjopen-2017-020781
|View full text |Cite
|
Sign up to set email alerts
|

Cushing’s sign and severe traumatic brain injury in children after blunt trauma: a nationwide retrospective cohort study in Japan

Abstract: ObjectiveWe tested whether Cushing’s sign could predict severe traumatic brain injury (TBI) requiring immediate neurosurgical intervention (BI-NSI) in children after blunt trauma.DesignRetrospective cohort study using Japan Trauma Data Bank.SettingEmergency and critical care centres in secondary and tertiary hospitals in Japan.ParticipantsChildren between the ages of 2 and 15 years with Glasgow Coma Scale motor scores of 5 or less at presentation after blunt trauma from 2004 to 2015 were included. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Moreover, a low heart rate value was associated with neurosurgery. The association of a high blood pressure and a low heart rate known as the Cushing's reflex corresponds to the adaptive response of the brain to severe intracranial hypertension [ 19 , 20 ]. It has already been demonstrated that this reflex was a predictor for neurosurgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a low heart rate value was associated with neurosurgery. The association of a high blood pressure and a low heart rate known as the Cushing's reflex corresponds to the adaptive response of the brain to severe intracranial hypertension [ 19 , 20 ]. It has already been demonstrated that this reflex was a predictor for neurosurgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…TBI that induces neuronal cell death and cerebral edema may cause increased intracranial pressure (IICP) ( 19 ). Severe IICP is associated with hypertension and bradycardia, known as the Cushing triad, which impairs SI accuracy ( 20 , 21 ). Odom et al ( 15 ) reported a bimodal relationship between SBP and mortality in a TBI population.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to studies in people that assessed the ability of the Cushing reflex to predict impending brain herniation secondary to severe traumatic brain injury. [15][16][17] In human trauma patients, several multicenter retrospective cohort studies suggested that the Cushing reflex is a weak but important predictor of severe traumatic brain injury requiring immediate intervention in adults and children after severe blunt trauma. 15,16 Similarly, in this study, significantly higher SBP-HR in dogs with brain herniation compared to the control group highlights the nature of the Cushing reflex.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In human trauma patients, several multicenter retrospective cohort studies suggested that the Cushing reflex is a weak but important predictor of severe traumatic brain injury requiring immediate intervention in adults and children after severe blunt trauma. 15,16 Similarly, in this study, significantly higher SBP-HR in dogs with brain herniation compared to the control group highlights the nature of the Cushing reflex. The most notable finding was that a higher SBP-HR with a cutoff value of >60 provides 90% specificity when diagnosing dogs with brain herniation.…”
Section: Discussionmentioning
confidence: 99%